Effect of pesticide types on community structure of arthropod in soy crops - Dwi Ristyadi; Nigel Andrew; Rachel Waugh (Jurnal Entomologi Indonesia, 2013)
This study was carried out on three soybean farms located in the Liverpool Plains Shire in New South Wales, Australia. The soybean farms were different in terms of pesticide type used. One of the soy crops was sprayed with broad spectrum synthetic pesticides (synthetic pyrethroids), one site of soy crop was sprayed with natural pyrethrum - an organically certified pesticide, and one of the soy crops was not treated with any pesticides. Arthropod samples were collected on three occasions at every site except in the third site of soy crops which was not treated with any pesticides. Samplings were done using sweep nets and beat sheets. There were no significant differences of community structure change between farms treated with different pesticide regimes (F2,5= 4.2599, P(perm)= 0.188), and no significant differences in arthropod species richness. The abundance of arthropods was significantly different for site treated with biopesticide and site treated with synthetic pyrethroids (G6 = 284.36, P <0.0001), non-sprayed site and site treated with synthetic pyrethroids (G6 = 2110, P < 0.0001), and non-sprayed site to site treated with biopesticide (G6 = 2027, P < 0.0001). The use of synthetic pesticides in agriculture has been found to suppress pests and beneficial arthropods, while the use of biopesticides or without pesticide, to some extent, may let beneficials thrive in the system and also may suppress pest arthropods.